Organisational characteristics that facilitate gender-based violence and harassment in higher education? - Pat O'Connor; Margaret Hodgins; Dorian Woods; Elisa Wallwaey; Rachel Palmen; Marieke Caroline Lisette van den Brink; Evanthia Kalpazidou Schmidt (Administrative Sciences, 2021)
Gender-based violence and sexual harassment (GBVH) by and towards academics and students has been under-theorised at an organisational level in higher education institutions (HEIs). The methodology involves a critical review of the literature on GBVH and organizational responses to it, locating it in the context of an analysis of organizational power. The theoretical perspective involves a focus on power and workplace bullying. It identifies three power-related characteristics of academic environments which it is suggested facilitate GBVH: their male-dominant hierarchical character; their neoliberal managerialist ethos and gender/intersectional incompetent leadership which perpetuates male entitlement and toxic masculinities. These characteristics also inhibit tackling GBVH by depicting it as an individual problem, encouraging informal coping and militating against the prosecution of perpetrators. Initiating a discussion and action at organizational and state levels about GBVH as a power-related phenomenon, challenging the dominant neo-liberal ethos and the hierarchical character of HEIs, as well as reducing their male dominance and increasing the gender competence of those in positions of power are seen as initial steps in tackling the problem.
Keywords: 350; higher education; gender incompetent leadership; gender-based violence and harassment; intersectionality; male dominated hierarchical structures; neoliberal managerialism; organisational approach; power